2015
DOI: 10.1021/acs.jpclett.5b01629
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitous Structural Signaling in Bacterial Phytochromes

Abstract: The phytochrome family of light-switchable proteins has long been studied by biochemical, spectroscopic and crystallographic means, while a direct probe for global conformational signal propagation has been lacking. Using solution X-ray scattering, we find that the photosensory cores of several bacterial phytochromes undergo similar large-scale structural changes upon red-light excitation. The data establish that phytochromes with ordinary and inverted photocycles share a structural signaling mechanism and tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 41 publications
(72 reference statements)
2
37
0
Order By: Relevance
“…This shows that the DrBphP PSM is principally capable of controlling both histidine kinase and phosphatase activities in dependence of light. Consistent with this observation, the well-studied conformational changes of the DrBphP PSM during the Pr-to-Pfr transition 26,29,55 are generally very similar across various phytochromes 38 , indicating that both histidine kinase and phosphatase modules can be controlled with other phytochrome photosensory modules.…”
Section: The Bacteriophytochrome From D Radiodurans Is a Light-activsupporting
confidence: 61%
See 1 more Smart Citation
“…This shows that the DrBphP PSM is principally capable of controlling both histidine kinase and phosphatase activities in dependence of light. Consistent with this observation, the well-studied conformational changes of the DrBphP PSM during the Pr-to-Pfr transition 26,29,55 are generally very similar across various phytochromes 38 , indicating that both histidine kinase and phosphatase modules can be controlled with other phytochrome photosensory modules.…”
Section: The Bacteriophytochrome From D Radiodurans Is a Light-activsupporting
confidence: 61%
“…Intriguingly, DrBphP lacked autokinase or phosphotransfer activities both in the Pr and Pfr state ( Figure 3A). The absence of kinase activity is surprising as the DrBphP and its PSM evidently undergo light-induced structural changes that seem to be conserved among other phytochromes 29,38,39 . All homologous bacteriophytochrome HKs studied to date exhibited light-dependent kinase activity.…”
Section: Agp1 Functions As a Histidine Kinase But Drbphp Acts As A Phmentioning
confidence: 99%
“…Millisecond time-resolved X-ray scattering was recorded at the Coherent Small-Angle X-ray Scattering (cSAXS) beamline at the Swiss Light Source as previously described 19 . The station uses a rapid-readout detector to detect the time-evolution of the X-ray scattering signal after reaction initiation with a laser pulse 20 .…”
Section: Methodsmentioning
confidence: 99%
“…The available Pr and Pfr PCM structures, including those of bathy‐BPhys and A. thaliana PhyB, largely conform to the scenario laid out for Dr BPhy. Comparative analyses by X‐ray solution scattering revealed that the light‐induced structural changes within the PCM associated with the Pr → Pfr transition are similar across several BPhys . Hence, it appears likely that the above signaling mechanism generally holds for Phys although it is open to which extent bathy and plant Phys differ.…”
Section: Photosensory Inputmentioning
confidence: 99%
“…Pfr transition are similar across several BPhys. 110 Hence, it appears likely that the above signaling mechanism generally holds for Phys although it is open to which extent bathy and plant Phys differ. With but few exceptions, the PCMs have been structurally elucidated in isolation, that is, as PAS-GAF-PHY constructs without covalently attached C-terminal effector module.…”
Section: Bacteriophytochrome Signalingmentioning
confidence: 99%